2003
DOI: 10.1021/ma020527r
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Maleic Anhydride Grafted Polyethylene by High-Resolution Solution-State NMR and FTIR Spectroscopy

Abstract: The microstructure of maleic anhydride (MA) grafted polyethylene (PE), MA-g-PE, has been successfully characterized by high-resolution NMR and FT-IR spectroscopy. The carbonyl asymmetric and symmetric stretchings of MA-g-PE exhibit lower shifts with an increase in the grafting degree of MA, suggesting stronger inductive interactions between different grafts in a solid state. The 1H and 13C NMR spectroscopy of [2,3-13C2]MA grafted PE with a low molecular weight (lmPE), [2,3-13C2]MA-g-lmPE, demonstrates that [2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 29 publications
3
48
0
2
Order By: Relevance
“…It is obvious from these figures the presence of new peaks at 1720 cm -1 and at 1787 cm -1 when MAH is grafted successfully onto PE. The band at 1787 cm -1 is due to the asymmetric stretching modes of carbonyl (C=O) group of saturated maleic anhydride, units while the band at 1720 cm -1 belongs to the symmetric stretching of carbonyl (C=O) of maleic acid grafted onto PE [20][21][22]. …”
Section: Ft-ir Spectroscopy Of Pe-g-mahmentioning
confidence: 99%
“…It is obvious from these figures the presence of new peaks at 1720 cm -1 and at 1787 cm -1 when MAH is grafted successfully onto PE. The band at 1787 cm -1 is due to the asymmetric stretching modes of carbonyl (C=O) group of saturated maleic anhydride, units while the band at 1720 cm -1 belongs to the symmetric stretching of carbonyl (C=O) of maleic acid grafted onto PE [20][21][22]. …”
Section: Ft-ir Spectroscopy Of Pe-g-mahmentioning
confidence: 99%
“…Despite the number of publications on the topic, there are still some discussions on particular reactional mechanisms [11,[24][25][26][27]. However, in a general way and according to Nachtigall et al [28], we can propose the following simplified mechanism: the free radicals generated by the peroxide decomposition lead by hydrogen abstraction to tertiary alkyl polymer radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The MA grafted to thermoplastic polymer can increase the polarity, which leads to better adhesion with biofillers 8 that have polar groups on their surfaces. Some works in the literature have proposed the use of MA grafted to thermoplastics as polyethylene and polypropylene [8][9][10][11][12][13] to improve the interfacial adhesion between the matrix and some reinforcement agents, as oak wood flour 5 , bamboo pulp fiber 14 , kenaf fiber 4 , clay 6,13,15 , bio-flour-filled 8 and others. It was observed that the presence of the compatibilizer agent induces a stronger interfacial adhesion and improvement of the mechanical properties, compared to uncompatibilized composites 4,15 , besides improving the particle dispersion into polymer matrix 13 , and the thermal stability of composite 8 .…”
mentioning
confidence: 99%